Predicting pubic arch interference in prostate brachytherapy on transrectal ultrasonography-computed tomography fusion images - Fukada, Junichi (Oxford University Press, 2012)
We investigated the usefulness of the fusion image created by transrectal ultrasonography (TRUS) and large-bore computed tomography (CT) for predicting pubic arch interference (PAI) during prostate seed brachytherapy. The TRUS volume study was performed in 21 patients, followed by large-bore computed tomography of patients in the lithotomy position. Then, we created TRUS-CT fusion images using a radiation planning treatment system. TRUS images in which the prostate outline was the largest were overlaid on CT images with the narrowest pubic arch. PAI was estimated in the right and left arch separately and classified to three grades: no PAI, PAI positive within 5 mm and PAI of >5 mm. If the estimated PAI was more than 5 mm on at least one side of the arch, we judged there to be a significant PAI. Brachytherapy was performed in 18 patients who were evaluated as not having significant PAI on TRUS. Intra-operative PAI was observed in one case, which was also detected with a fusion image. On the other hand, intra-operative PAI was not observed in one case that had been evaluated as having significant PAI with a fusion image. In the remaining three patients, TRUS suggested the presence of significant PAI, which was also confirmed by a fusion image. Intra-operative PAI could be predicted by TRUS-CT fusion imaging, even when it was undetectable by TRUS. Although improvement of the reproducibility of the patients’ position to avoid false-positive cases is warranted, TRUS-CT fusion imaging has the possibility that the uncertainty of TRUS can be supplemented.